2019
DOI: 10.5455/msm.2019.31.202-206
|View full text |Cite
|
Sign up to set email alerts
|

Fecal and Urinary Incontinence Associated with Pregnancy and Childbirth

Abstract: Introduction:Fecal incontinence (FI) and urinary incontinence (UI) are major problems faced by women worldwide, with pregnancy and delivery representing two major risk factors for these conditions. The prevalence of FI and UI varies across studies. In our region, only a few publications have addressed this topic.Aim:The aim of this study was to determine the prevalence of FI and UI in Saudi pregnant women, their characteristics, and a specific clinical pattern that could identify patients that are at a risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
1
0
3
Order By: Relevance
“…The study presented in 2019 included 393 respondents. Th e authors reported that 84 respondents (21.4%) experienced the development of leakage of urine aft er the vaginal childbirth [14]. A long--term study investigating the leakage of urine aft er the childbirth with a range of up to 12 years was published in 2015, the results pointing up to the incidence urinary incontinence in 33.1% 3 months aft er the childbirth (1247 women from 3763 respondents), 6 years aft er the childbirth the incidence was in 46.8% and er 12 years aft er the childbirth the incontinence was found in 52.7% [15].…”
Section: Discussionmentioning
confidence: 99%
“…The study presented in 2019 included 393 respondents. Th e authors reported that 84 respondents (21.4%) experienced the development of leakage of urine aft er the vaginal childbirth [14]. A long--term study investigating the leakage of urine aft er the childbirth with a range of up to 12 years was published in 2015, the results pointing up to the incidence urinary incontinence in 33.1% 3 months aft er the childbirth (1247 women from 3763 respondents), 6 years aft er the childbirth the incidence was in 46.8% and er 12 years aft er the childbirth the incontinence was found in 52.7% [15].…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies stating that high BMI is a risk factor for POP [6,19,27]. In a cross-sectional study conducted in the Netherlands, overweight women (BMI > 25) prevalence was reported to increase in women with a history of POP and SUI surgery [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, un estudio encontró que no había diferencia en la función del piso pélvico o sexual entre aquellas mujeres que tuvieron un parto instrumental sin complicaciones (exitoso) y aquellas que tuvieron parto por cesárea (14). Mientras un estudio encontró que la asociación de parto vaginal con IU se limitaba a aquellos sin episiotomía (15) otros autores encontraron que el riesgo de IU aumentaba en los casos de laceración perineal o episiotomía (16,17). Esta diferencia puede estar relacionada con la asociación entre características de la episiotomía y disfunción del piso pélvico.…”
unclassified
“…La laceración perineal, del esfínter y la episiotomía se asocian con un riesgo más alto de IF (16,17). La gravedad de la laceración perineal, ya sea espontánea o por una episiotomía, durante el parto vaginal, parece constituir el factor más determinante de IF posterior al parto.…”
unclassified
See 1 more Smart Citation